PRIVATIZATION OF SOLID WASTE MANAGEMENT: OPPORTUNITIES AND CHALLENGES - Yahya Muhammed Bah; Myrtati Dyah Artaria (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Aim: The fundamental rationale for a systematic literature review is to examine opportunities and challenges in the privatization of solid waste management, and share knowledge to spark and inspire a process that will usher in public private partnership to ensure cities are kept clean for habitability. Methodology and Results: A systematic review of the literature using information obtained from different sources was performed. The Google Search Engine was used to search for these articles. During the search numerous combinations of words and phrases were used to ensure articles reflect the most recent knowledge and scholarly works. Only peer-reviewed articles published after 2000 were selected, except extracts perceived to be of fundamental mileage to the study. However, articles published by staunch international organizations working in privatization of solid waste management for years which had produced indefatigable knowledge in the field were stealthily appraised. The privatization of solid waste management has resulted in some successes which include, but not restricted to: effectiveness, cost saving, timely service delivery, access to funding and expansion, quality services, partnership and community participation, cleanliness and healthy environment, jobs creation and better income, elimination of public monopoly and promotion of competition, new technologies and innovative techniques, public sector concentration on supervision, resources conservation and protection from risks; less bureaucracy and prompt action regarding concerns and complaints. Conclusion, significance and impact of study: With a well-thought model and proper public supervision, the privatization of solid of waste management can deliver habitable cities, though not without negative impacts and obstacles.